Experimental Study on Shear Behavior and Acoustic Emission Characteristics of Nonpersistent Joints - Yujing Jiang; Yongqiang Chen; Xianzhen Cheng; Hengjie Luan; Sunhao Zhang; Qizheng Zhao; Wei Han (Geofluids)
The shear behavior of rock discontinuities controls the stability of rock masses to a great extent. In this paper, laboratory shear tests were performed on rock-like materials with different cracks to study the effect of nonpersistent joints on the shear behavior of rock masses. The results show that the variation trends of the shear stress-displacement curves of specimens with different cracks are generally similar and have the same stage characteristics. When the crack length is relatively short, the elastic stage is prolonged, the peak shear strength decreases, and the shear displacement corresponding to the peak shear strength and the residual shear strength increases with the increase of the crack length. When the crack length is relatively long, the elastic stage is shortened, the peak shear strength decreases, and the shear displacement corresponding to the peak shear strength increases with the increase of the crack length. The peak shear stress gradually decreases with the increase of the crack length. The shear strength of the specimens with unilateral cracks is much higher than that of the specimens with bilateral cracks. The shear strength of the specimens is affected not only by the crack length but also by the crack distribution. The acoustic emission (AE) count peak occurs when the shear stress drops sharply and has an inverse “S”-type variation trend with the increase of the crack length. The inclination angle of the fracture decreases, the roughness of the fracture surface decreases, and the proportion of the wear area on the fracture surface increases gradually with the increase of the crack length. The AE source decreases with the increase of the crack length, and their locations are obviously asymmetric. This work can greatly contribute to the insight into the shear failure mechanism of rock discontinuities with nonpersistent joints.